Features of blood parameters and adaptational status of Balb/c and C57Bl/6 mice lines in the absence of special influences - G. V. Zhukova; E. M. Frantsiyants; A. I. Shikhlyarova; I. V. Kaplieva; L. K. Trepitaki; P. S. Kachesova; A. V. Galina; N. D. Ushakova; E. V. Shalashnaya; O. G. Ishonina (Южно-Российский онкологический журнал, 2023)
Purpose of the study. A comparative analysis of blood parameters and some characteristics of the adaptation status of intact Balb/c and C57Bl/6 mice of both sexes.Materials and methods. We investigated intact mice of both sexes belonging to the C57Bl/6 (n = 18) and Balb/c (n = 20) lines. The age characteristics of these animals corresponded to the first half of the reproductive period. We studied the parameters of the complete and biochemical blood tests, the weight characteristics of the thymus, spleen and adrenal glands. The character and tension of general nonspecific adaptational reactions of the body (AR) were assessed as well. In statistical analysis we used the coefficient of variation (CV), Student's t-test, Mann-Whitney test.Results. In mice of both studied lines, the dominance of females over males was noted in terms of the weight characteristics of the thymus and spleen, the development of the most favorable antistress AR, and the number of indicators with low variability. At the same time, in C57Bl/6 mice, animals of different sexes had a similar nature of AR (AR of elevated activation),but differed in signs of tension, this might indicate the difference in the range of levels of reactivity, appropriate to AR in males and females C57Bl/6. Unlike C57Bl/6, mice Balb/c mice of different sexes were distinguished with the predominant antistress AR. Differences between C57Bl/6 mice and Balb/c mice in terms of amylase and ALT activity indicated a shift towards carbohydrate metabolism in Balb/c mice and a shift towards protein metabolism in C57Bl/6 mice. Animals of the С57Bl/6 line had an advantage over Balb/c mice (especially pronounced in females) in some indicators of the adaptation status.Conclusion. The results of the study indicated possible difference in the ratio of carbohydrate and protein metabolism in the animals of the studied lines and testified a more favorable state of the regulatory systems in C57Bl/6 mice compared to animals of the Balb/c line. The revealed regulatory and metabolic interlinear differences can determine the features in the reaction of the body of animals belonging to different lines to the malignant process and efficiency of antitumor therapy.